Interlocking Nail Combined with Locking Plate Fixation for a Distal Diaphysis Femur Comminuted Fracture in a Dog - Andrade Moutinho da Conceicao, Maria Eduarda Bastos [UNESP]; Santos, Levi Oliveira dos; Sembenelli, Guilherme [UNESP]; Dias Lima, Carolina Goncalves [UNESP]; Salvitti de Sa Rocha, Thiago Andre [UNESP]; Minto, Bruno Watanabe [UNESP]; Gosuen Goncalves Dias, Luis Gustavo [UNESP] (Univ Fed Rio Grande Do Sul, 2018)
Background: Interlocking Nail (ILN) is similar a solid intramedullary pins with screws or bolts passing through one and nail holes (locking effect). This implant mostly have been putted normograde, passing by trochanteric fossa of femur, although it is reported to be inserted through the knee, passing by fracture focus and ending close to proximal femur. It is carried out especially when there is a comminuted fracture in distal third shaft of femur. Locking plate systems work as internal fixators with some advantages compared to conventional plates. It can be used combined with intramedullary pin, and is an effective technique for increase stifeness stabilization of comminuted long-bone fractures, especially for bending. Some studies reported the use of plate-nail to increase even more the stiffness of implants, because of locking screw in plate and nail. Based on the same propose, we aim to report a case of an ILNs normograde (from distal to proximal) connected to a locking plate in highly comminuted distal diaphyseal fracture since it is rarely report in veterinary medicine orthopaedics. Case: A 5-year-old male mixed breed dog was assessed and diagnosed a fracture of the femur in the right pelvic limb. On physical examination, the dog had nonweight bearing lameness in the affected limb and, mobility of the fragments was noted following digital pressure. A comminuted fracture of the distal diaphysis of the femur was identified. A lateral approach to the shaft of the femur, the incision was extended to the stifle joint through a lateral incision because the fracture seemed to extend throughout the physis. Open but do not touch approach was performed and reduction was gotten without modified environment of fracture hematoma. A surgical drill was inserted through the access in distal extremity of the bone to open the medullary cavity of the femur. After that, an interlocking nail was inserted into the opening into the distal fragment, the fracture was reduced and the nail was inserted towards the proximal end of the bone. At the next stage the nail was fitted into the medullary canal and it was locked relative to the main fragments of the femur using locking head screws that were anchored in the load carrier of the plate. Postoperative radiographic views documented appropriate implants location and satisfactory femur fracture alignment. At 3 weeks, the patient showed functional use of the limb with partial weight bearing. Discussion: A biomechanical study comparing plate-rod and plate-nail system in gap fractures, showed that maximum load was significant different between the groups, and in plate-nail it was always heavier, it occurs because of the nail bigger diameter and screws pass through nail holes. What prove that this system is stiffer than plate-rod, so because this patient has osteopenia and thin cortical bone like showed previously, we preferred to use nail than intramedullary pin. The ILN could be introduced from proximal to distal femur (antegrade or normograde) and passing through the knee (called in medicine by retrograde, although in veterinary medicine this way is called normograte too), it depends on bone contbrmation. Several studies used normograde via in femur from distal to proximal, especially in distal fracture. In this case, it was used this via, by the knee, because it would promote better bone stock to insert the screws, since the nail was putted as close as possible from articular surface. In conclusion, the case reported here documented that the combination of a nonnograde (from distal to proximal) interlock nail with a locking plate provides a rigid fixation method, promoting satisfactory functional recovery time. Further investigations should be performed using plate-nail in vivo to give to us more precise data.
Keywords: biological osteosynthesis; canine; orthopaedics; retrograde nail